2011
DOI: 10.4028/www.scientific.net/kem.462-463.563
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thermal Prestress on the Deformation of Micromirror Chip Embedded with Through-Silicon Vias

Abstract: The thermal expansion mismatch problem for a chip due to temperature decrease from processing temperature to room temperature may cause residual stress inside the chip structure. The thermal prestress accumulated and may affect the chip reliability when the chip was subjected to the thermal loading again. In this paper, the effect of thermal prestress on the micromirror chip embedded with copper through-silicon vias (TSVs) was investigated by the finite element method. In analysis, the micromirror chip embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The results showed that the pressure sensitivity was remarkably affected by various geometries of the protection gel. In 2011, Yeh and Lu (2011) evaluated the effect of thermal prestress in the operating process for a micromirror chip and proposed a three-step finite element method to obtain the stress distribution in the chip. The results showed that the maximum von Mises stress increased around four times as compared to that shown in the prestress analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the pressure sensitivity was remarkably affected by various geometries of the protection gel. In 2011, Yeh and Lu (2011) evaluated the effect of thermal prestress in the operating process for a micromirror chip and proposed a three-step finite element method to obtain the stress distribution in the chip. The results showed that the maximum von Mises stress increased around four times as compared to that shown in the prestress analysis.…”
Section: Introductionmentioning
confidence: 99%
“…There is no best solution yet for the selection of materials, especially from the viewpoint of reliability. Although numerous studies (Batra et al , 2008; Chou et al , 2009; Kim et al , 2015; Kwak and Park, 2015; Lishchynska et al , 2007; Ruan et al , 2017; Yeh and Lu, 2011, 2016) have reported the influence of thermal loading on the performance and reliability of MEMS chips, very few papers have focused on residual stress analysis of the shielding electrode. Particularly, the shielding electrode, which is used to prevent pull-in, requires stress analysis because its dimensions are not yet small enough.…”
Section: Introductionmentioning
confidence: 99%